Molecular basis of rotavirus virulence: role of gene segment 4. - Offit, P A (J Virol, 1986)
Bovine rotavirus NCDV and simian rotavirus SA-11 exhibited markedly different patterns of gastrointestinal tract disease when inoculated orally into newborn mice. A genetic approach was used to define the molecular basis of these differences. The SA-11 strain of rotavirus was more virulent than the NCDV strain when inoculated orally into newborn mice; the dose of SA-11 required to cause diarrhea in 50% of infant mice was 50-fold less than that required for NCDV. Nineteen reassortant viruses were derived by coinfection of MA-104 cells in vitro with the SA-11 and NCDV strains. The parental origin of reassortant virus double-stranded RNA segments was determined by gene segment migration differences in polyacrylamide gels and hybridization with radioactively labeled parental viral transcripts. The neutralization antigen phenotype of reassortant viruses was determined by plaque reduction neutralization. We found that the dose of SA-11 and NCDV rotavirus required to induce gastroenteritis in newborn mice was determined by gene segment 4. The results suggest that rotavirus virulence may be manipulated by modification or reassortment of gene segment 4. IMAGES: